2016
DOI: 10.3324/haematol.2016.144535
|View full text |Cite
|
Sign up to set email alerts
|

A sequential approach with imatinib, chemotherapy and transplant for adult Ph+ acute lymphoblastic leukemia: final results of the GIMEMA LAL 0904 study

Abstract: In the GIMEMA LAL 0904 protocol, adult Philadelphia positive acute lymphoblastic leukemia patients were treated with chemotherapy for induction and consolidation, followed by maintenance with imatinib. The protocol was subsequently amended and imatinib was incorporated in the induction and post-remission phase together with chemotherapy. Due to the toxicity of this combined approach, the protocol was further amended to a sequential scheme based on imatinib plus steroids as induction, followed by consolidation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 52 publications
0
54
0
1
Order By: Relevance
“…The 3 patients received a mean of 10 monthly infusions (range, [6][7][8][9][10][11][12][13]. No immediate infusion-related adverse events were observed, and no grade 2-4 toxicities, including development of cytokine release syndrome, attributable to the T-cell infusions were recorded during follow-up.…”
Section: Cd8mentioning
confidence: 99%
See 1 more Smart Citation
“…The 3 patients received a mean of 10 monthly infusions (range, [6][7][8][9][10][11][12][13]. No immediate infusion-related adverse events were observed, and no grade 2-4 toxicities, including development of cytokine release syndrome, attributable to the T-cell infusions were recorded during follow-up.…”
Section: Cd8mentioning
confidence: 99%
“…1,4 Prolonged hematologic and cytogenetic remissions have been observed with imatinib mesylate (IM) alone, even in the presence of persisting levels of minimal residual disease (MRD). [5][6][7] Our group was able to demonstrate that attainment of such clinical responses directly correlated with the emergence of BCR-ABL-specific T cells in the bone marrow (BM) and, to a lesser extent, in the peripheral blood of nonallografted Ph 1 ALL patients undergoing postremission maintenance treatment with either IM or other second-generation TKIs. 8,9 These observations extended previous evidence of functional leukemia-specific cellular immune responses developing in patients receiving IM, and possibly acting in synergy with IM to reach disease control, 10,11 and represent the basis for a combined TKI and T-cell therapy approach to Ph 1 ALL in elderly patients, or in patients relapsing after alloHSCT.…”
mentioning
confidence: 99%
“…40 Other studies have also reported the occurrence of ABL1 kinase domain mutations at relapse. 18,19,47 These data suggest that development of ABL1 kinase domain mutations, and particularly T315I, is an important contributor to the development of relapse in Ph 1 ALL suggesting that a more potent inhibitor with activity against the resistanceinducing mutations, such as ponatinib, is likely to be beneficial in this disease. Indeed early reports of use of this agent in the frontline setting have suggested impressive activity with high response rates including high and early CMR rates.…”
Section: Patientmentioning
confidence: 93%
“…15 However, a patient unable or unwilling to undergo transplantation likely requires the combination of ALL-based chemotherapy regimens with TKIs. 18,19 Potential benefits of the more intensive regimens including high doses of cytarabine and methotrexate may include deeper disease eradication and better central nervous system (CNS) penetration.…”
Section: Introductionmentioning
confidence: 99%
“…In acute promyelocytic leukemia, the identification of specific genetic lesion(s), which imply exquisite sensitivity to targeted differentiating therapy, have led to the development of chemotherapy-free treatment approaches, such as the combination of all- trans retinoic acid (ATRA) and arsenic trioxide (ATO) [ 10 , 11 ], endowed with 100% complete response (CR) rate and no toxic deaths or induction of resistance, particularly when MRD is monitored by sensitive techniques, such as RT-PCR, as in the Italian AIDA trial [ 12 ]. Other examples include chronic myeloid leukemia (CML), in which life-expectancy of affected patients now approaches that of the general population after the introduction of different generations of tyrosine kinase inhibitors (TKI) [ 13 ] and the development of molecularly-based MRD monitoring strategies [ 14 , 15 ]; similarly, molecularly-based prognostic stratification and combined TKI-based treatment strategies have led to the implementation of chemotherapy-free induction regimens endowed with 97-100% CR rates and no induction deaths in Philadelhpia + ALL [ 16 ], suitable for the safe and effective treatment even of patients aged >90 years. In chronic lymphocytic leukemia (CLL), molecular characterization by high-throughput technologies are redefining risk groups and paving the way for truly individualized treatment strategies, based on the availability of a wealth of drugs targeted to specific molecular aberrations [ 17 ]; similarly, the discovery of pathogenic BRAF mutations in hairy cell leukemia (HCL) has had diagnostic and therapeutic implications [ 18 ].…”
Section: Clinical Trials and Companion Diagnostics In Hematology Andmentioning
confidence: 99%